Promising Practices for Leadership Development: Exploring a Collaborative Professional Learning and Coaching Program - Thomas, Christy; Koehn, Jennette; Turner, Jeff (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2024)
Given the substantial impact school leaders have on school improvement, the imperative for continuous professional learning for leaders is evident. In this two-year action research study, researchers collaborated with a school division, forming a research-practice partnership, to design and explore a collaborative professional learning and coaching program. The primary objective of this program was to align with local leadership standards and foster leadership development. The central research question was: How does implementation of a collaborative professional learning and coaching program contribute to leadership development? Data were collected from district and school leaders and included pre and post surveys, interviews, and focus groups. The findings of this study indicate that district leadership practices show promising potential in fostering inservice opportunities for leadership development. These practices include the following: (a) ensure programs are sustained with a consistent focus, (b) utilize collaborative learning approaches, (c) assess growth through reflection and feedback, and (d) use action research to support continual improvement. This study aims to provide valuable insights to school districts and researchers regarding the implementation of sustained and job-embedded professional development for school leaders, with a specific focus on leadership development.